Against Representation: il teatro di Einar Schleef - Kolesch, Doris (Kritik. Rivista di letteratura e critica culturale, 2024)
Thies essay focuses on Einar Schleef’s theatre. Schleef provokes and fascinates so much mainly because he uses an original and highly personal theatrical language that stands in strong friction with the hegemonic theatrical aesthetic. To this Schleef opposes an aesthetic of overwhelm that operates with large choral masses, with excessive vocalizations produced by choirs that not only speak and sing, but also frequently shout. The tight rhythms of these performances rehearse a very intense, sometimes violent stimulation and solicitation of the body and senses, both as far as the actor and the spectator are concerned.